The Method of Takhrīj Hadîts 'Lâwasiyyata liwâritsin' and Its Implications for the Understanding of the Takhshish al-Qur’an by the Hadīts in Inheritance law - Eti Maryati (International Journal of Islamic Khazanah, 2019)
The hadith prohibits the will is authentic as the Hadith because of the idhafah of the Prophet SAW, and the Hadith is revealed in thirteen books of the mashâdir al-ashliyyah, and fulfills the element of the Hadīts, an eternal consisting of 136 rawi sanad. Honesty of the Hadiths Prohibition of the Will to the Heirs in terms of the number of rawi including Muthat because narrated by many friends without seeing the quality of the material and raw so that it includes Qath'i al-wurûd and Qath'i dilâlah. Based on the rules of tashhih, if seen from a part of the rawi mate that collapsed, including da'eef and could not rise to hasan so mardud. For sanad who are ghair matruk, the term is hasan lighairihi which appears because there is mutabi and shaheed. Surat al-Baqarah verse 180 regarding the obligation to make a will can be compromised by inheritance verses by seeing it as a provision that each has a different target. The verses on inheritance specialize the provisions of a will that are general in nature and in the inheritance verses of Surah al-Nisa verses 11-12, show some of the afrad (material) testament obligations that are general to those who inherit only. Because there is a problem in understanding the will can be haram, makruh / mubah. In practice in daily life, the will is needed to bring good to the heirs who are likely to share the inheritance with other heirs. A will is an alms intended to draw closer to Allah SWT, it also becomes one of the ways to equalize inheritance for those who do not get inheritance rights while they are close relatives